Sexual violence and the Criminal Justice System in Ghana: Exploring the issues of victim protection and confidentiality in the court - Hutchful, Ebenezer (Department of Public Law, 2021)
The protection of survivors of sexual violence during court proceedings is as important as the court proceedings themselves, as any mishaps may impact greatly on the well-being and future engagement of these survivors with the criminal justice system. The issue of secondary victimization remains a problem faced by many survivors of sexual violence who try to seek justice for their ordeal. It is against this background that several international, regional and national documents have been enacted with hopes of mitigating the issue of secondary victimizations from the criminal justice system and its actors. The court as an institution within the criminal justice system is established to handle all criminal and civil cases within a defined jurisdiction and as such is charged to handle all cases of sexual violence filed before it. However, the role of the court in protecting victims especially victims of sexual violence is increasingly being questioned. Therefore, the dissertation seeks to explore the issues surrounding the protection of survivors of sexual violence in the Ghanaian court. To adequately explore the issue under consideration, a qualitative research approach was adopted, which entailed on-site observations and interviews. As a case study, the gender court was selected as the site for the research. The findings of the study support a strong argument for an expansive approach from the court and all stakeholders of the criminal justice system, from both structural and legal approaches as well as the need for an attitudinal change to harness the protection of survivors of sexual violence who seek justice for their ordeal. Thus, the findings point to the need for urgent attention to help reduce the risk of secondary victimization in the court.